ANALISIS MODAL KERJA DAN LIKUIDITAS UNTUK MENGETAHUI PROFITABILITAS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE TAHUN 2009-2012 - Renato Bastian Manurung (Universitas Katolik Widya Karya Malang, 2019)
The purpose of the research is to assess the financial performance of property and real estate companies (PT Alam Sutera Realty Tbk, PT Ciputra Property Tbk and PT Bukit Darmo Property Tbk) listed on BEI period 2009-2012. The type of research is documentation on IDX, data source in the form of secondary data, financial performance assessment by using ratio analysis especially working capital ratio, liquidity ratio and profitability ratio.The result of analysis shows from 3 (three) property and real estate companies listed on BEI in 2009-2012 period that have the best value of the three ratio analysis (working capital ratio, liquidity and profitability) are PT. Ciputra Property Tbk, followed by PT. Alam Suteta Realty Tbk and the last one is PT. Bukit Darmo Property Tbk. Kata Kunci: Analysis, Financial Ratios, Financial Performance